0025 Gene-based Analysis of Iron Related Pathways associated with Sleep-Disordered Breathing in Trans Omics in Precision Medicine (TOPMed). (12th April 2019) - Wang, Heming; Cade, Brian E; Lee, Jiwon; Sofer, Tamar; Zhu, Xiaofeng; Redline, Susan
Abstract: Introduction: Although OSA is heritable, few significant genetic associations have been observed in genome-wide association analyses largely because of limited power. Recent research suggest a novel role of iron metabolism in the pathophysiology of OSA, including metabolic and inflammatory pathways as well as ventilatory control mechanisms involving carotid body respiratory chemoreceptors. We aim to further study the underlying genetics linking iron metabolism pathways and OSA using deep sequencing data collected by NHLBI Trans-Omics for Precision Medicine (TOPMed) program. Methods: We focused on 72 genes from three iron/heme-related pathways (heme metabolism process, iron ion homeostasis, and cellular iron ion homeostasis), and performed gene-based association analyses with four OSA-related phenotypes (apnea hypopnea index [AHI], average and minimum oxygen saturation during sleep, and percentage sleep time with oxygen saturation <90%) in 8, 021 individuals of multi-ancestry from 7 cohorts. OSA phenotypes were rank normalized and adjusted for age, sex, BMI, smoking, ancestry, and relatedness. Secondary analyses were performed in specific for each ancestry group. The significance level was P<0.0007 after correcting for multiple comparisons. Results: The overall sample was 58 years old and included 56% women with a median AHI of 7.4. Primary multi-ancestry analysis identified that AHI was significantly (P=5.02×10 -4 ) associated with an aggregate effect of functional variants in the enhancer region of BTBD9, a gene previously associated with restless leg syndrome and circadian rhythm. Gene-based analysis using variants at gene enhancer regions demonstrated stronger associations than using variants at gene coding regions, which may reflect regulatory role of gene enhancers. Secondary ancestry stratified analyses additionally identified significant associations in CYBRD1, SOD1, and TFRC . Suggestive evidence was observed in multiple iron-related genes, including the previous identified FECH . Conclusion: This study supports the important role of iron/heme-related pathway in OSA independent of obesity and smoking. In next step, we will incorporate gene expression data from TOPMed to further understand the biological mechanisms behind the genetic associations. Support (If Any): Sleep Research Society Foundation (SRSF) Career Development Award 018-JP-18 (HW) and NIH grands R01HL113338 (SR), R35 HL135818 (SR).